Rancangan Welding Fixture Pembuatan Produk Front Engine Mounting Mobil Suzuki Baleno - Prassetiyo, Hendro; Rispianda, ; Dewi, Puspita (Universitas Katolik Parahyangan, 2015)
Manufacture industry develops very rapidly, it could be seen from the various technology that is used inthe process of the production. This developments causes the increasing of consumers needs, so the businessmenof manufacture have to be able to increase the quality and quantity of the products that are produced. Oneof the way to increase it that is by using aids of productions which are Jig and Fixture. This paper is talkingabout the design of Welding Fixture which this kind of fixture is always used for welding processes. Theseaids are used for the welding process of front engine mounting cars products of Suzuki Baleno. The design ofwelding fixture is done to decrease the defects of the products caused by the less precise components placementwhen the welding process is underway. Moreover, the design is done to hasten the processes of loading andunloading (setup).